Implementation of the CLIL-Based 'One-Presenter Five-Interrogators' Technique to Improve the Oral Argumentation Skills of KPNK Cadets - Deliani, Meriah Kita (Jurnal Bahasa Indonesia Prima (BIP), 2026)
The implementation of an Outcome-Based Education (OBE) curriculum in maritime vocational higher education requires a transformation of the learning process oriented towards competency outcomes. This study describes the implementation of the Content and Language Integrated Learning (CLIL)-based 'One-Presenter Five-Interrogators' technique in improving cadets' oral argumentation skills and critical reasoning. Using descriptive qualitative Classroom Action Research (CAR) conducted in two cycles, all 60 Semester 2 cadets of the KPNK Study Program at Politeknik Adiguna Maritim Indonesia Medan participated without a separate control group. Quantitative indicators showed improvements in: (a) cadets independently identifying field problems (10% to 72%); (b) analytical questions posed by interrogators (0% to 65%); and (c) presenter confidence ratings (mean 1.8 to 3.4 on a 4-point rubric). Data were collected through participatory observation, field notes, and problem draft documentation. Results indicate significant transformation in cadets' critical reasoning, from only 10% able to identify problems independently to being more analytical in mapping port operational phenomena. The 1:5 interaction technique created "professional pressure" triggering public speaking courage and sharper oral arguments. CLIL integration strengthened maritime literacy through accurate technical terminology use. The 'One-Presenter Five-Interrogators' technique proves effective in building argumentation and negotiation skills needed for industrial work practices and maritime marketing careers.